2005
DOI: 10.1007/s11033-004-5908-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Response of Bombyx Mori Calreticulin

Abstract: We isolated a calreticulin cDNA from the silkworm, Bombyx mori. The cDNA encodes 398 amino acid residues of B. mori calreticulin, with an endoplasmic reticulum retentional HDEL motif at its C-terminus and a predicted molecular mass of 45,801 Da. The B. mori calreticulin shows high protein homology with calreticulin from G. mellonella (88%), A. aegypti (71%), D. melanogaster (69%) and H. sapiens (63%). The highest level of mRNA expression of B. mori calreticulin was exhibited in the fat body of this insect. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Further more, calreticulin located in the endoplasmic reticulum, has been implicated in many diverse functions, including: regulation of intracellular Ca 2+ homeostasis, chaperone activity, steroid-mediated gene regulation, and cell adhesion [58]. The highest level of mRNA expression of calreticulin was exhibited in the fat body of Bombyx mori [59]. Our result showed that calreticulin was identified during the initial embryogenesis both in D and ND samples, which means that calreticulin is essential during embryonic development.…”
Section: Resultsmentioning
confidence: 53%
“…Further more, calreticulin located in the endoplasmic reticulum, has been implicated in many diverse functions, including: regulation of intracellular Ca 2+ homeostasis, chaperone activity, steroid-mediated gene regulation, and cell adhesion [58]. The highest level of mRNA expression of calreticulin was exhibited in the fat body of Bombyx mori [59]. Our result showed that calreticulin was identified during the initial embryogenesis both in D and ND samples, which means that calreticulin is essential during embryonic development.…”
Section: Resultsmentioning
confidence: 53%
“…Recently, the calreticulin gene ( BmCRT ) was cloned and characterized from B . mori (Goo et al . 2005).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4, the transcripts of PxCRT are almost undetectable in the fat body, are expressed at higher levels in both midgut and Malpighian tubules and peak in the silk glands. Recently, the calreticulin gene (BmCRT) was cloned and characterized from B. mori (Goo et al 2005). Northern blot analysis shows that BmCRT is mainly expressed in the fat body, not the silk glands.…”
Section: Overexpression Of Pxcrt Transcripts In Silk Glandmentioning
confidence: 99%
“…The up-regulation of CRT expression level also might be attributed to the chaperone function and Ca 2? homeostasis (Goo et al 2005;Luana et al 2007). ROSinduced lipid peroxidation also leads to the loss of ability of endoplasmic reticular membranes (Lehotsky et al 2002), and ultimately to trigger the production of Ca 2?…”
Section: Responses Of Stress Protein Gene Expressionmentioning
confidence: 99%